FEATURES OF INDONESIAN ENGLISH (INDOLISH): A SOCIOLINGUISTIC ANALYSIS - Yetty Yetty; Sri Ayu Budi Lestari (Bajang Institute, 2022)
This study aims to describe the features of linguistics items in Indolish as well as the register or style and the code switching. It used both oral and written data which were collected by in-depth interview of the participants who work as a bank officer. The data were analyzed by descriptive and qualitative analysis. The result of the study shows that the linguistics features of Indonesian English are omission, overgeneralization, and substitution. It also found that some of technical terms related to register using or style such as annual fee, analyst, approve, credit card, credit, payment, a credit loan, debtor, account officer, debtors’ data, System Information of Debtors (SID), loan, offering letter, loan agreements, credit disbursement, a funding officer, customer, and customer fun. Moreover, the phenomenon of code switching occurs based on the data as the characteristics of Indolish because the participants lack of their vocabulary in English and they do the code switch in order to make their interlocutor understand of what they have been said